The city in the memorial gestures of Zero Hora’s Cultura supplement: the chronotope of the chronicle and the columnists (Intercom - Brazilian Journal of Communication Sciences, 2022)
This article is the result of the research Journalism, memory and city: study of the supplement Cultura of Zero Hora (2011-2014), which problematize the memorable gestures of a cultural supplement in the journalistic representation of the city. Here, we analyzed the chroniclers Luís Augusto Fischer, Ricardo Chaves e Ismael Caneppele who had fixed columns in the suplemment, considering that they are a special point of view about the city, mediators governed by the experiences of living and belonging. Based on the narrative analysis, we focus on the representations of the city proposed by the chroniclers, the ways in which they move around it, the map they affectively inhabit, which places receive visibility and value resulting in a singular topography. We find in the cultural supplement an environment propitious for the fusion of signs that characterize the chronotope, that is, time indexes that appear in space and, vice versa, the space that makes sense because it's measured by time.
Keywords: Chronicle; City; Supplement Cultura (ZH); Cultural Journalism; Chronotope